How do consumers perceive private labels? Perceptual map of private labels offered by the three largest food retailers in Brazil - Furquim, Thiago Campos; Paula, Verônica Angélica Freitas de; Ruy, Marcelo (Revista de Administração da UFSM, 2015)
Private labels present an alternative to the manufacturer’s brands. Brazilian food retailers have increased the investment in private labels and it is justified as private labels may help develop loyalty, profit margins and competitive differentiation. However, researches concerning the perception of private labels´ image are not common, being possible to highlight some national studies. In this sense, this study aims at investigating how consumers perceive the positioning of private labels offered by the three largest food retailers in Brazil (in terms of gross sales). To achieve these objectives, a perceptual map is developed. It also aims at understanding the respondents´ profile to verify possible differences in the perception of private labels´ image evaluated from demographic variables such as gender and family income. Field research was developed through surveys, aiming to capture the respondents´ perception of private labels in two ways: when the respondent was free to assess the similarity between the studied private labels; and when the evaluation dimensions were given. The analysis of the retailers´ institutional websites was conducted to identify the positioning of each of the studied private labels, namely: Great Value, Bom Preço and Sentir Bem (Walmart); Viver and Carrefour (Carrefour); Extra, Casino, Taeq and Qualitá (Pão de Açúcar). The questionnaire was administered electronically, using "Google Forms". Using a non-probability convenience sampling, 264 completed questionnaires were received. As it was decided to build the perceptual map based only on respondents who evaluated all of the studied private labels, 42 cases (or 15.9% of respondents) were considered. From the results obtained it was possible to group the set of responses into categories and to construct a perceptual map from the general synthesis of two maps: one obtained by overall similarity, and another one obtained by considering the dimensions Variety, Price and Packaging. Both maps were developed using the Multidimensional Scaling. Results show that there is a partial convergence between them and indicate the possibility of another unifying attribute.